Social and Economic Conditions for Innovation Development of Russian Regions - N. E. Bondarenko (Plekhanov Russian University of Economics, 2019)
The efficient social and economic development of the Russian Federation is impossible without sustainable development of its entities, which implies well-balanced regional economy based on advanced production, housing and public utility, transport and other types of infrastructure; the development of social sphere and provision of favourable living conditions for the population; elimination of misbalances in regional development. At the same time the social and economic development of our country gradually acquires the innovation orientation, which sets new goals for state aimed at ensuring sustainable dynamics of innovation processes at the regional level. The essential condition of the country and its regions innovation development is the effective regulating impact on the whole totality of lines, which could raise innovation activity and competitiveness of different levels. The authors analyzed Russia's positions in the global innovation index, studied the index components, which could give the country an opportunity to get high results of innovation activity and those indicators, where Russia is lagging behind the majority of countries. The authors showed the factors hindering the impact on innovation processes both in quantitative and qualitative indicators of innovation activity. Leaning on statistic data the authors analyzed key social factors influencing conditions and results of innovation development in regions for the last decade and highlighted principle problems hindering innovation processes.